Hernia de Amyand - Vargas- Córdova, Ronnal (2016)
Amyand’s hernia is an unusual diagnosis where the cecal appendix is part of the hernial sac contents in an inguinal hernia. It shows a case report of a 71-year-old male patient with a diagnosis of right inguinal hernia treated surgically. Amyand’s hernia was an intraoper tive finding. It performed an appendectomy and hernioplasty with favorable clinical evolution. It discharged on the second postoperative day without complications..